Robotic Arm Innovations: Addressing Emerging Healthcare Challenges - Madan Jagtap; Prajapati Vaibhav Brajesh; Shitole Gaurav Rajaram; Mudliyar Saravanan Kartik; Nalawde Jivraj Ashok (International Journal of Advanced Robotics and Automation Technology, 2024)
This Robotic arm is programmable in nature and nature, be manipulated. The robotic arm is also occasionally appertained to be as anthropomorphic as it's veritably analogous to that of mortal hand. Robots are extensively used for variety of tasks that are considered too dangerous to be performed by humans the rapid-fire progress in robotic fashion provides new openings for biomedical and healthcare engineering presently, there's an adding population of cases suffering from covid- 19 influenza, respiratory syncytial contagion, Bordetella pertussis infection (whooping cough), Staphylococcus aureus infections of the nose and throat and different allergies in addition, we look at the developments in AI and machine learning that improve robotic arms' capacity to adapt to challenging medical tasks. This paper attempts to clarify the critical role that robotic arms will play in influencing the future of healthcare delivery and enhancing patient outcomes by combining current knowledge and pointing out future directions.
Keywords: : Robotic arm; AI; Bacteria; COVID-19; Infection; virus